2018
DOI: 10.37358/rc.18.4.6220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Considerations Regarding Stress and Arrhythmic Risk in Patients with Chronic Viral Liver Diseases

Abstract: The prevalance of depression and anxiety is higher at the patients diagnosticated with viral liver disease. The corelation between stress and chronic liver disease is a natural, implicit one, but still insufficiently studied. The study has the objective of finding out the clinical and also biochemical correlations between stress and chronic viral diseases. Our research was realised on a group of 78 patients with chronic viral liver disease, who underwent an evaluation of the stress level, both from a subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Like our results, many other studies concluded that there is a codependence between the digestive dysfunction and impairment of quality of life [18,19].…”
Section: Results and Discusionssupporting
confidence: 89%
“…Like our results, many other studies concluded that there is a codependence between the digestive dysfunction and impairment of quality of life [18,19].…”
Section: Results and Discusionssupporting
confidence: 89%
“…The markers that contribute to decreased the quality of life is stigma, memory loss, motor impairment and digestive dysfunction, especially drooling [16,17]. In our analysis the digestive dysfunction only correlated with the quality of life in patients with continuous administration of L-dopa/carbidopa.…”
Section: Resultsmentioning
confidence: 59%
“…Dividing the analysed cases according to their Her2 status was definitive following in situ hybridization and included 12 her2 positive cases (12%) and 88 Her2 negative cases (88%), placing them within the 10-34% interval of all mammary carcinomas that had an over-expression of the HER2 receptor and that are usually associated with a poor prognosis [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%